Efficacy and Safety of Sinomenine Preparation for Ankylosing Spondylitis: A Systematic Review and Meta-Analysis of Clinical Randomized Controlled Trials. (15th May 2020) - Lin, Shan-Shan; Liu, Chun-Xiang; Zhang, Jun-Hua; Wang, Hui; Zhai, Jing-Bo; Mao, Jing-Yuan; Wang, Xian-Liang
Abstract : Objectives . To systematically evaluate the efficacy and safety of sinomenine preparation (SP) for treating ankylosing spondylitis (AS). Methods . Clinical randomized controlled trials (RCTs) of SP for treating AS were systematically identified in six electronic databases including PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), Chinese Scientific Journal Database (VIP), and Wanfang Databases from the inception up to 31 October 2019. Cochrane's risk of bias tool was used to assess the methodological quality and Review Manager 5.3 software was used to analyze data. Results . A total of 12 RCTs involving 835 patients were finally included. According to interventions, RCTs were divided into two types. The intervention in 10 RCTs was SP combined with conventional pharmacotherapy (CPT) versus CPT and that in 2 RCTs was SP alone versus CPT. The results of the meta-analysis showed that, compared with CPT alone, SP combined with oral CPT has better improvement in BASDAI (WMD = −1.84, 95% CI [−3.31, −0.37], P = 0.01 ), morning stiffness time (WMD = −13.46, 95% CI [−16.12, −10.79], P < 0.00001 ), the Schober test (WMD = 1.26, 95% CI [0.72, 1.80], P < 0.00001 ), the occipital wall test (WMD = −0.55, 95% CI [−0.96, −0.14], P = 0.009 ), the finger-to-ground distance (WMD = −3.28, 95% CI [−5.64, −0.93], P = 0.006 ), 15 m walking time (WMD = −8.81, 95% CI [−13.42, −4.20], P = 0.0002 ), the C-reactive protein (CRP) (WMD = −1.84, 95% CI [−3.24, −0.45], P = 0.01 ), and the total effective rate (RR = 1.10, 95% CI [1.01, 1.20], P = 0.03 ). Besides, it also showed that oral SP alone may be more effective in improving morning stiffness time (WMD = −31.89, 95% CI [−34.91, −28.87], P < 0.00001 ) compared with CPT alone. However, this study cannot provide evidence that loading the injectable SP based on CPT can significantly increase the efficacy due to the insufficient number of studies included. In terms of adverse events, there was no statistically significant difference between the experimental group and the control group. Conclusions . This study shows that oral SP may be effective and safe in the treatment of AS. Due to the low methodological quality of the included RCTs and the limitations of the meta-analysis, it is still necessary to carry out more multicenter, large-sample, and high-quality RCTs to further verify the conclusions. The review protocol was registered on PROSPERO (CRD42018099170 ), and the review was constructed following the PRISMA guidelines (Annex 1).